Plasticity in Pro- and Anti-tumor Activity of Neutrophils: Shifting the Balance - Furumaya, Charita; Martinez-Sanz, Paula; Bouti, Panagiota; Kuijpers, Taco W.; Matlung, Hanke L. (Frontiers in Immunology, 2020)
Over the last decades, cancer immunotherapies such as checkpoint blockade and adoptive T cell transfer have been a game changer in many aspects and have improved the treatment for various malignancies considerably. Despite the clinical success of harnessing the adaptive immunity to combat the tumor, the benefits of immunotherapy are still limited to a subset of patients and cancer types. In recent years, neutrophils, the most abundant circulating leukocytes, have emerged as promising targets for anti-cancer therapies. Traditionally regarded as the first line of defense against infections, neutrophils are increasingly recognized as critical players during cancer progression. Evidence shows the functional plasticity of neutrophils in the tumor microenvironment, allowing neutrophils to exert either pro-tumor or anti-tumor effects. This review describes the tumor-promoting roles of neutrophils, focusing on their myeloid-derived suppressor cell activity, as well as their role in tumor elimination, exerted mainly via antibody-dependent cellular cytotoxicity. We will discuss potential approaches to therapeutically target neutrophils in cancer. These include strategies in humans to either silence the pro-tumor activity of neutrophils, or to activate or enhance their anti-tumor functions. Redirecting neutrophils seems a promising approach to harness innate immunity to improve treatment for cancer patients.